Microplásticos em alimentos de origem vegetal na cidade de Itacoatiara (AM), Brasil - (:unkn) unknown (ICET - Instituto de Ciências Exatas e Tecnologia (Itacoatiara), 2026)
Microplastics are practically ubiquitous contaminants in all environments on the planet. Therefore, the present work aimed to investigate microplastic contamination in lettuce, chives, and cilantro sold in Itacoatiara, Central Amazon, Brazil. Samples of each vegetable were acquired from different commercial establishments. The samples were washed with filtered distilled water to remove any particles present on the surface of the vegetables. Hydrogen peroxide was added to the water used to wash the vegetables to digest organic materials. The solution was stirred daily and kept in an oven at 60°C. The microplastic particles were separated using the density difference technique. In total, 247 microplastic particles were recorded. There was no significant difference in the number of microplastic particles per sample of the three types of vegetables. The size of the microplastic particles also did not differ significantly between the types of vegetables, with the smallest (0.067 mm) and largest (4.865 mm) particles being found in lettuce. The proportion of microplastic colors recorded on the vegetables varied significantly. Blue and red particles were predominant, with a greater abundance of blue particles (n=207; 83.8%). There was a significant difference in the proportion of microplastic particle formats, with fibers (n=235; 95.1%) being more representative than fragments (n=12; 4.9%). Thus, it can be confirmed that the vegetables sold in Itacoatiara, Central Amazon are contaminated, consequently unsafe for direct human consumption, and require washing with plenty of running water to eliminate microplastic particles before being consumed fresh.
Microplastics in plant-based foods in the city of Itacoatiara (AM), Brazil
Keywords: Contaminação por plástico; Alimentos vegetais; Plásticos em alimentos; Contamination by plastic; CIENCIAS BIOLOGICAS; Alimentos - Contaminação; Alimentos - Análise; Hortaliças - Contaminação